2016
DOI: 10.3847/0004-637x/827/2/104
|View full text |Cite
|
Sign up to set email alerts
|

Quasars as a Tracer of Large-Scale Structures in the Distant Universe

Abstract: We study the dependence of the number density and properties of quasars on the background galaxy density using the currently largest spectroscopic data sets of quasars and galaxies. We construct a galaxy number density field smoothed over the variable smoothing scale of between approximately 10 and 20 h −1 Mpc over the redshift range 0.46<z<0.59 using the Sloan Digital Sky Survey (SDSS) Data Release 12 (DR12) Constant MASS galaxies. The quasar sample is prepared from the SDSS-I/II DR7. We examine the corre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 92 publications
(135 reference statements)
1
11
0
Order By: Relevance
“…We found that X-ray AGN trace the distribution of X-ray clusters at a <25-45 Mpc scale: the fraction of agglomerates located in the vicinity of X-ray clusters is ∼1.5-2 times higher than for randomly distributed agglomerates in both considered redshift ranges. This is in agreement with Arnold et al (2009) and also with optical AGN studies by Hwang et al (2012) and Song et al (2016), where the authors show that the AGN fractions in the field environment are higher than in clusters. Kocevski et al (2009) found that Seyfert-2 galaxies avoid the densest regions of superclusters and are instead located in intermediate density environments.…”
Section: Large-scale Structure Of the Xxl-ssupporting
confidence: 91%
See 3 more Smart Citations
“…We found that X-ray AGN trace the distribution of X-ray clusters at a <25-45 Mpc scale: the fraction of agglomerates located in the vicinity of X-ray clusters is ∼1.5-2 times higher than for randomly distributed agglomerates in both considered redshift ranges. This is in agreement with Arnold et al (2009) and also with optical AGN studies by Hwang et al (2012) and Song et al (2016), where the authors show that the AGN fractions in the field environment are higher than in clusters. Kocevski et al (2009) found that Seyfert-2 galaxies avoid the densest regions of superclusters and are instead located in intermediate density environments.…”
Section: Large-scale Structure Of the Xxl-ssupporting
confidence: 91%
“…This is in agreement with previous works for AGN selected in the optical, X-ray, and radio (cf. Gilmour et al 2009;Constantin et al 2008;Silverman et al 2009;Lietzen et al 2009Lietzen et al , 2011Tasse et al 2008Tasse et al , 2011Melnyk et al 2013;Hwang et al 2012;Gendre et al 2013;Manzer & De Robertis 2014;Karouzos et al 2014a,b;Song et al 2016). On the other hand, according to the small-scale analysis, the Kolmogorov-Smirnov probability that the AGN overdensity distribution is consistent with the mock distribution is less than 10 −3 in the first redshift range and for both the bright and faint environments.…”
Section: Small-and Large-scale Environments Of X-ray Agnmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, previous studies show that quasar pairs at low redshift (z < 1) do not always reside in dense environments. A recent study by Song et al (2016) shows that z ∼ 1 single quasar environments have a slight tendency toward high density regions, while the enhancement of the quasar density is weaker than expected from a proportional relation of the galaxy density. From this section, we extend the redshift range down to z ∼ 1 to compare with the high-redshift pairs and also with single quasars at the same redshift.…”
Section: Quasar Pairs At Z ∼mentioning
confidence: 88%